In Silico Evaluation of Quinoline Derivatives as PfLDH Inhibitors through Molecular Docking, Lipinski’s Rule, and ADMET Profiling - Livia Putrima Rijas; Amalia Putri Lubis; Rahadian Zainul; Meksim Rebezov; Vikash Jakhmola; Tarek Elkhooly; Dini Liya Meirani Simatupang; Yolandha Putri (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2026)
This study aimed to evaluate quinoline-spiro derivatives as potential inhibitors of P. falciparum lactate dehydrogenase (PfLDH), a key enzyme involved in parasite energy metabolism, using an in silico approach. Molecular docking was performed to assess ligand-protein interactions, followed by drug-likeness evaluation based on Lipinski's Rule of Five and pharmacokinetic-toxicity prediction using ADMET analysis. The results showed that all tested compounds exhibited favorable binding interactions with PfLDH, thus demonstrating potential as enzyme inhibitors. Several compounds exhibited stronger binding affinity than reference ligands, suggesting that structural modifications with the spiro framework enhance interaction with the target protein. Most compounds also met drug-likeness criteria, although there were minor deviations. Among the compounds evaluated, one candidate, (Z)-2-((2-(7- chloroquinolin-4 -yl) hydrazinyl) methyl) -4-(3- methylbenzylidene)-2-azaspiro[4.5] decan-3-one showed the most balanced profile, based on results obtained by combining strong binding interactions with favorable pharmacokinetic properties and predicted low toxicity. Quinoline-spiro derivatives may be promising candidates for the development of antimalarial drugs targeting PfLDH. This study describes the integrated in silico evaluation of quinoline-spiro derivatives as PfLDH inhibitors, as drug candidates for further development.